To be or to do: Effective Characteristics of Teachers of Children with Developmental Disorders and Disabilities - Safa Al-Ali (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study reports on the results of a qualitative phenomenographic study that aims to determine the effective characteristics of teachers of children with developmental disorders and disabilities in Jordan, and to identify the best practices that can be implemented in the field of special education in Jordan. To achieve the objectives of the study, semi-structured interviews were conducted with (35) university students receiving training in special education centers within the requirements of field training. The researcher transcribed and manually collected participants' experiences and responses using phenomenological and thematic analyses. The results of the main research question showed two sets of characteristics: there was a clear consensus on the role of personal and moral characteristics of teachers on the one hand, and on the professional and academic qualities on the other hand. The results of the second question showed some considerations related to professional practices during the service. The results of the study indicate the need to reconsider the policies and mechanisms of admission to higher education programs and emphasize the importance of in-service vocational training, which ensures continuous, appropriate and effective education for children with disabilities.